PENGARUH PROFESIONALISME DAN ETIKA PROFESI TERHADAP BUDAYA DISIPLIN MAHASISWA - Irianto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
Discipline is self-awareness that arises from the deepest inner self to follow and obey the rules, values and laws that apply in a particular environment. This awareness includes, among other things, that if someone is able to be well disciplined it will have a good impact on their future success. Therefore, researchers conducted scientific research on the influence of professionalism and professional ethics on the disciplinary culture of students majoring in Engineering at the Bontang College of Industrial Technology. The approach used in this research is a quantitative approach. A quantitative approach is a scientific way to obtain data with specific purposes and uses based on numbers and statistics. This research was carried out on the STTIB campus and the target respondents were STTIB campus students for 3 months by distributing a survey in the form of a Google form containing several questions. Based on research regarding the influence of professionalism and professional ethics on the disciplinary culture of students majoring in engineering at STTI Bontang, it can be concluded that these two factors have a significant role in forming and strengthening a disciplinary culture among students. Professionalism, which includes students' ability to apply their technical knowledge and skills as best as possible, makes a positive contribution to disciplinary attitudes and behavior. Professional ethics also have an important impact, because students who have moral awareness and integrity in carrying out their technical tasks tend to be more compliant with applicable rules and norms. In other words, an understanding of moral responsibility as an engineering professional helps strengthen the culture of discipline in the academic environment